Babel subjetiva ou a mais completa tradução: considerações sobre Budapeste de Chico Buarque - Martha-Toneto, Diana Junkes Bueno [UNESP] (My University, 2014)
This paper discusses aspects of Budapest, by Chico Buarque, published in 2003. In the novel, a contingency takes the protagonist, a Brazilian, to Hungary. There, involved within a culture quite distinct from his, he has experiences in a strange language, which “even the devil respects”, and with an interesting woman, who teaches him the language. Both, language and woman, turns into mirrors that refract and put his subjective experience, as babelic as the Hungarian, up side down. Considering contingency as a category from the Real (Lacan) and translation as mechanism of subjective search of a blot origin (Derrida), at the same time transcreation (Haroldo de Campos), we will pinpoint some ways to the novel reading.

Este artigo discute aspectos de Budapeste, de Chico Buarque, publicado em 2003. No romance, uma contingência leva o protagonista, um brasileiro, à Hungria. Lá, envolvido com uma cultura distinta da sua, aventura-se em experiências com uma língua estranha, que “até o diabo respeita”, e com uma mulher instigante, que lhe ensina essa língua. Ambas convertem-se em espelhos que refratam e invertem sua experiência subjetiva tão babélica e incompreensível quanto aquela que Budapeste lhe impõe. A partir da consideração da contingência como categoria do Real (Lacan) e da tradução como mecanismo de busca da subjetividade e rasura da origem (Derrida) ao mesmo tempo que transcriação (Haroldo de Campos), serão apontados alguns caminhos para a leitura do romance.
Subjective Babel or the most complete translation: some considerations on Budapeste by Chico Buarque
Keywords: Budapeste; subjetividade; tradução; contingência; metalinguagem; subjective; translation; contingency; metalinguistic